Web based Information system for selling spare parts and custom bicycle frames (Case Study Of The Surabaya Minion Shop) - muhammad Hendra Oktaviano; Arif Senja Fitrani (Procedia of Engineering and Life Science, 2021)
The purpose of this research is to design and produce an Online Shop application that is a Web that can provide information on goods data related to the sale of spare parts and custom frames that they are looking for. The research method used is the waterfall method, while the techniques for data collection use observation and interview techniques. The spare part data is obtained from visiting from shop to shop and the shop itself. The result of this research is to make it easier for customers to find the spare parts they want and to make more and more bicycle enthusiasts, especially onthel mini bikes, use them.